2020
DOI: 10.15252/msb.20209701
|View full text |Cite
|
Sign up to set email alerts
|

The GENDULF algorithm: mining transcriptomics to uncover modifier genes for monogenic diseases

Abstract: Modifier genes are believed to account for the clinical variability observed in many Mendelian disorders, but their identification remains challenging due to the limited availability of genomics data from large patient cohorts. Here, we present GENDULF (GENetic moDULators identiFication), one of the first methods to facilitate prediction of disease modifiers using healthy and diseased tissue gene expression data. GENDULF is designed for monogenic diseases in which the mechanism is loss of function leading to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 89 publications
(124 reference statements)
0
2
0
Order By: Relevance
“…In this study, knocking down SRSF3 or hnRNP A1 increases full-length SMN expression consistent with previous findings. We also re-identified U2AF1 and PUF60 that have been previously reported to suppress SMN exon 7 inclusion ( Auslander et al, 2020 ; Hastings et al, 2007 ). Together, we found that siRNA targeting almost all the previously confirmed genes that promote SMN exon 7 exclusion is indicative of the robustness of the screening strategy.…”
Section: Discussionmentioning
confidence: 66%
“…In this study, knocking down SRSF3 or hnRNP A1 increases full-length SMN expression consistent with previous findings. We also re-identified U2AF1 and PUF60 that have been previously reported to suppress SMN exon 7 inclusion ( Auslander et al, 2020 ; Hastings et al, 2007 ). Together, we found that siRNA targeting almost all the previously confirmed genes that promote SMN exon 7 exclusion is indicative of the robustness of the screening strategy.…”
Section: Discussionmentioning
confidence: 66%
“…Among the CF modifiers, He et al showed in a human nasal and bronchial tissue bulk RNAsequencing study that SLC6A14 is one of the most active co-expressing gene, with respect to both CFTR and other modifiers 15 . Here, we were able to detect significant co-expression with two of the most widely investigated modifier genes in CF, SLC26A9 and SLC6A14 [44][45][46][47][48][49] , with each other and with CFTR in AT2 cells. The expression of these two genes and CFTR are highest in AT2, sAT2, club, differentiating basal and goblet cells compared to the other cell types (Figure S13).…”
Section: Discussionmentioning
confidence: 67%